Konsep Pertanggungjawaban Pidana Pajak yang Dilakukan Wajib Pajak Perseroan Terbatas Guna Mewujudkan Kepastian Hukum - Sorialam, Mangottang; I, Ismail; Setiawan, Puguh Aji Hari (Media Hukum Indonesia (MHI), 2025)
This research aims to answer the still biased things of the main of the issue so that it can be beneficial for the development of legal science. To find the bright spot, then the author conducted research with the results of research revealed that criminal threats related to taxpayers are on the provisions of articles 38, 39, and 39A of the Criminal Code, but against PT can only be convicted of criminal threats. its criminal threat is an alternative between a fine penalty or a confinement penalty so it is relevant to apply to PT. Whereas section 39 and 39A are not logically applied to PT because the formulation of the criminal threat is cumulative in the form of offense of imprisonment and offense of fine whereby PT cannot be charged with offense of imprisonment. In addition, with regard to the entry into force of the National Criminal Code later, the arrangement of corporations as the subject of criminal action so that they can be requested criminal accountability will be illogical if applied to articles 39 and 39A of the Criminal Code due to criminal threats. The conclusion is that the provisions of criminal liability for taxes by PTs in the Constitution are still not fulfilled by legal certainty due to differences in interpretation of the law in the enforcement of laws related to criminal liability for taxes by corporations (PTs), so the author suggests that the revision is made before the Constitution contains the National Constitution. PT can be demanded criminal accountability and the threat of criminal sanctions.